2022
DOI: 10.1038/s43705-022-00118-3
|View full text |Cite
|
Sign up to set email alerts
|

Metabarcoding the Antarctic Peninsula biodiversity using a multi-gene approach

Abstract: Marine sediment communities are major contributors to biogeochemical cycling and benthic ecosystem functioning, but they are poorly described, particularly in remote regions such as Antarctica. We analysed patterns and drivers of diversity in metazoan and prokaryotic benthic communities of the Antarctic Peninsula with metabarcoding approaches. Our results show that the combined use of mitochondrial Cox1, and 16S and 18S rRNA gene regions recovered more phyla, from metazoan to non-metazoan groups, and allowed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 87 publications
2
17
0
Order By: Relevance
“…Here we present a pioneer study to establish the molecular biodiversity baselines of shallow hardbottom habitats from the WAP. This preliminary study, similar to what Fonseca et al (2017Fonseca et al ( , 2022 found in soft-bottom habitats, reveals that most of the benthic biodiversity found in Antarctic…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Here we present a pioneer study to establish the molecular biodiversity baselines of shallow hardbottom habitats from the WAP. This preliminary study, similar to what Fonseca et al (2017Fonseca et al ( , 2022 found in soft-bottom habitats, reveals that most of the benthic biodiversity found in Antarctic…”
Section: Discussionsupporting
confidence: 87%
“…Local patchiness and structure within these communities are probably a consequence of a combination of several biotic and abiotic factors (i.e. ice disturbance, food supply, competition, seabed topography and life-cycle strategies; Clarke et al, 2021;Fonseca et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study evaluating arctic benthic diversity similarly found that COI detected fewer taxa than 18S using eDNA metabarcoding, and there was only ~ 40% taxa overlap between markers at the class level 42 . In the current study, the COI marker using both nucleic acid templates yielded a higher percentage of unassigned taxa after filtering for presence in the majority of mesocosms compared to 18S.…”
Section: Discussionmentioning
confidence: 99%
“…Case-study examples of the applicability of both eDNA approaches to these four tasks are presented in BOX 1. eDNA metabarcoding can be used to describe species richness (e.g. in Leray and Knowlton, 2015;McClenaghan et al, 2020;Boulanger et al, 2021;Liu and Zhang, 2021;Sato et al, 2021;Yu et al, 2021;Fonseca et al, 2022;Good et al, 2022;Keck et al, 2022), surveillance of the presence/absence of target species such as invasive, or endangered (e.g. in Jerde et al, 2011;Boussarie et al, 2018;Holman et al, 2019;Bonfil et al, 2021;Manfrin et al, 2022), and monitor changes in species composition (e.g.…”
Section: Edna Data Analyses Pipelinesmentioning
confidence: 99%